Bilaterally prolonged latencies of pain-related evoked potentials in peripheral nerve injuries. (25th September 2018) - Fischer, Marc; Höffken, Oliver; Özgül, Özüm Simal; Maier, Christoph
Highlights: We elicited pain-related evoked potentials (PREP) in patients with nerve injuries. Latencies of PREP were prolonged bilaterally. Amplitudes of PREP were unchanged in comparison to controls and the unaffected side. Abstract: Objective: Cross-sectional study to test the applicability of pain-related evoked potentials (PREP) for the diagnosis of peripheral nerve injuries (PNI). Introduction: Patients with generalized polyneuropathies show prolonged latencies and decreased amplitudes of PREP indicating an impairment of A-delta fibers. Although these fibers are frequently affected in PNI, it is unclear, if PREP-testing detects PNI comparable to Nerve Conduction Studies (NCS). Methods: 23 patients with PNI of one upper limb underwent bilateral PREP-testing (using concentric surface electrodes) and NCS. 41 healthy controls underwent PREP-testing only. We determined pain thresholds, N1-latencies and N1P1-amplitudes of PREP and analyzed them for group and side-to-side differences. Small-fiber function was evaluated using thermal detection thresholds of Quantitative Sensory Testing (QST). N1-latencies above a cut-off calculated by ROC-analysis were defined as abnormal in order to compare detection rates of PREP and NCS. Results: Patients with PNI showed bilaterally prolonged N1-latencies (ipsilateral: 167.0 ± 40.7 ms vs. 141.2 ± 20.5 ms / contralateral: 160.0 ± 41.0 ms vs. 140.2 ± 23.9 ms) without a significant side-to-side difference. Pain thresholds were increased on the affected side only (4.6 ± 5.2 mA vs. 2.4 ± 1.4 mA (controls)). N1P1-amplitudes did not differ between patients and controls. 7 (32%) patients showed prolonged N1-latencies (>176 ms) of PREP. NCS were abnormal in 16 (73%) cases. 13 (59%) patients showed thermal hypoesthesia in QST. Conclusion: Contrary to our expectations, we found bilaterally prolonged N1-latencies and normal N1P1-amplitudes in patients with PNI. Our findings support the hypothesis of a bilateral generation of PREP and indicate that PREP are not suitable for the diagnosis of PNI.